Estimating the burden of diseases attributable to lead exposure in the North Africa and Middle East region, 1990-2019: a systematic analysis for the Global Burden of Disease study 2019 - Malihe Rezaee; Zahra Esfahani; Seyed Aria Nejadghaderi; Mohsen Abbasi-Kangevari; Sahar Saeedi Moghaddam; Ali Ghanbari; Azin Ghamari; Ali Golestani; Elmira Foroutan Mehr; Ameneh Kazemi; Rosa Haghshenas; Mahsa Moradi; et al. (BMC, 2022)
Abstract Background Lead exposure (LE) and its attributable deaths and disability-adjusted life years (DALYs) have declined in the recent decade; however, it remains one of the leading public health concerns, particularly in regions with low socio-demographic index (SDI) such as the North Africa and Middle East (NAME) region. Hence, we aimed to describe the attributable burden of the LE in this region. Methods Data on deaths, DALYs, years of life lost (YLLs), and years lived with disability (YLDs) attributable to LE in the NAME region and its 21 countries from 1990 to 2019 were extracted from the Global Burden of Disease (GBD) 2019 study. Results In 2019, the age-standardized death and DALY rates attributable to LE were 23.4 (95% uncertainty interval: 15.1 to 33.3) and 489.3 (320.5 to 669.6) per 100,000 in the region, respectively, both of which were higher among men than women. The overall age-standardized death and DALY rates showed 27.7% and 36.8% decreases, respectively, between 1990 and 2019. In this period, Bahrain, the United Arab Emirates, and Turkey had the highest decreases in the age-standardized death and DALY rates, while Afghanistan, Egypt, and Yemen had the lowest ones. Countries within high SDI quintile had lower attributable burden to LE compared with the low SDI quintile. Cardiovascular diseases and chronic kidney diseases accounted for the 414.2 (258.6 to 580.6) and 28.7 (17.7 to 41.7) LE attributable DALYs per 100,000 in 2019, respectively. The attributable YLDs was 46.4 (20.7 to 82.1) per 100,000 in 2019, which shows a 25.7% reduction (-30.8 to -22.5%) over 1990-2019. Conclusions The overall LE and its attributed burden by cause have decreased in the region from 1990-2019. Nevertheless, the application of cost-effective and long-term programs for decreasing LE and its consequences in NAME is needed.